Perlindungan Hukum Bagi Anak Sebagai Korban Tindakan Persetubuhan - Yolanda Puspita Dewi; Hervina Puspitosari (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
As a democratic country, Indonesia is one of the countries that has experienced an increase in the number of cases of sexual intercourse. These criminal acts occur mostly from the environment and the surrounding community. This despicable thing is a criminal act that tarnishes related to good rules of religion, immorality and decency. Currently this is also happening in big cities. For example, in the city of Surabaya, with the rise of cases of sexual intercourse, people are increasingly worried, especially their closest family members. This disgraceful act is part of a very serious legal customer and there must be strict and severe sanctions that must be stipulated so that a complex case study is necessary. In uncovering the case, there was such a despicable act that targeted the victim to the children of the perpetrator against the victim. Investigators need to understand the aspects that are the cause or factor of the existence of such a disgraceful act of intercourse with the victim among children so that the investigator can know how to do it by providing protection to victims of immoral acts towards children. The problems and objectives that are wanted in this scientific study with the aim of finding out and understanding the aspects that are the causes or factors for these immoral acts and understanding what obstacles the investigation team receives to explain the reasons for the disgraceful act of intercourse that targets child victims happened in the city of Surabaya. In addition, this research is also intended to find out what efforts are made by law enforcers to protect victims of these immoral acts, especially child victims and obstacles in deciding on these protection efforts. Implementation of this research is intended by carrying out steps such as interviews, literature review, or review of scientific references. The results of this study indicate that the legal protection provided by investigators is: medical examinations for victims of sexual intercourse, namely by carrying out Visum et Rapertum, the investigators carry out rehabilitation for victims by presenting a psychologist to restore the disturbed psyche of the victim, this is very important to do.